A comparison of the use of normal saline versus Ringer`s lactate in the fluid resuscitation of diabetic ketoacidosis - Jivan, Daksha (My University, 2013)
OBJECTIVE To determine whether there are differences in time to resolution of diabetic ketoacidosis (DKA) and in the occurrence of biochemical abnormalities in adult patients who received either normal saline or Ringer’s lactate as initial fluid resuscitation. RESEARCH DESIGN AND METHODS This prospective observational study compared outcomes in patients who received either normal saline (n=22) or Ringer’s lactate (n=18) as initial fluid therapy during the acute management of DKA. RESULTS Median time to resolution of DKA did not differ between the two groups [normal saline 18.5 hours (IQR 9-25) compared to Ringer’s lactate 17 hours (IQR 10-24); p=0.23]. There were also no significant differences in the incidence of hypernatraemia, hyperchloraemia or worsening acidosis between the groups. CONCLUSION Either normal saline or Ringer’s lactate may be used as initial fluid resuscitation in DKA as neither fluid conferred a benefit in time to resolution of DKA or in the occurrence of biochemical abnormalities.